Landscape ecological approach in managing ecotourism in Gua Musang, Kelantan - Rabi'atul Adawiyah Ismail (2014)
The primary objective of this study is to identify the land use activity and landscape structure pattern in 3 places in Gua Musang, Kelantan which are Jedip Village, Gua Madu and Ketitir Lakes for future sustainable ecotourism site planning using Geographical Information System(GIS) as a tool. The area of this study is based 3 condition which is forest, caves and water that closely related to ecotourism spots.lt was specifically chosen by an activity with the help of Geographical Information System (GIS) to analyse the spatial data on land use land cover data on 2006 and landscape structure analysis integrated with other GIS datasets to establish the relationship between the landscape structure on the pattern of land use and ecotourism activity in Jedip Village, Gua Madu and Ketitir Lakes at a district level in Gua Musang province. The final step of this study was the priority to use landscape ecology approach in managing ecotourism activity in this 3 area that contribute and achieve the best practice on healthy ecosystems and quality well-being of the community. The result is useful for tourism facilities development, management and ecotourism resource utilization where ecotourism could be more developed. Additionally, the results can be used for managers and planners working in local and central governments and other non-governmental organizations. These integrated approaches cover complex and universal issues such as sustainable development of ecotourism, biodiversity conservation and protected area management in a tropical and developing country such as Malaysia Furthermore, ecotourism can also act as a starting point for research in sustainable development to form sustainable ecotourism for the needs and wants of environmental stability and socio-economic with more complex studies in the future.